(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Maxillofacial surgery is a highly specialized field of medicine that addresses a wide range of congenital, traumatic, inflammatory, and oncological conditions affecting the facial and jaw regions. Effective organization of medical care in this field is essential for timely diagnosis, appropriate treatment, and comprehensive rehabilitation of patients. This article aims to analyze the organization of medical care for the population in the field of maxillofacial surgery, focusing on the structure of healthcare services, levels of care delivery, patient referral pathways, and the role of multidisciplinary collaboration. Particular attention is given to the accessibility of specialized care, continuity of treatment, and the integration of modern medical and digital technologies. The analysis demonstrates that a well-structured system of maxillofacial surgical care contributes to improved clinical outcomes, reduced complication rates, and enhanced quality of life for patients.